HUBUNGAN ANTARA MOTIVASI KERJA PERAWAT DENGAN KEPUASAN KERJA PERAWAT DI INSTALASI RAWAT INAP BADAN RUMAH SAKIT UMUM DAERAH KABUPATEN BATANG - Anik Indriono; Zaenudin . (LPPM Universitas Pekalongan, 2012)
Abstract This study is aimed at gaining information on the degree of nurses’work motivation and nurses’work satisfaction in the inpatient ward and to know whether or not there is a correlation between the two variables. Methode: This study belongs to descriptive correlational study with cross sectional approach. The instrument used in this study is questionnaire given to 55 nurses in the inpatient ward of BRSUD Kabupaten Batang. The data are processed and analyzed quantitatively using univariat and bivariat analysis. The Bivariat analysis uses Rank Spearman test. Significance is determined by p-value < 0.05. Result: The results of the study shows that sub variable of the nurses’ work motivation having significant correlation with the nurses’ work satisfaction is the motivation of power. This is shown by significance test where significance value (p-value is 0.029) < 0.05. This is probably because the respondents have the perception that working is a way to gain personal satisfaction by getting power and by using the power to ward others.Increasing nurses’ work motivation and nurses’ work satisfaction can be understaken through the management of BRSUD Kabupaten Batang by giving job enrichment, enlarging participation and independence, rotation and appropriate placement according to their competence, giving freedom to serve patient and by acknowledgment and rewrd based on their achievement.Key words : Work motivation and work satisfaction